2021
DOI: 10.3762/bjoc.17.52
|View full text |Cite
|
Sign up to set email alerts
|

Designed whole-cell-catalysis-assisted synthesis of 9,11-secosterols

Abstract: A method for the synthesis of 9,11-secosteroids starting from the natural corticosteroid cortisol is described. There are two key steps in this approach, combining chemistry and synthetic biology. Stereo- and regioselective hydroxylation at C9 (steroid numbering) is carried out using whole-cell biocatalysis, followed by the chemical cleavage of the C–C bond of the vicinal diol. The two-step method features mild reaction conditions and completely excludes the use of toxic oxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Starting material 2 was recovered in 36% yield (72 mg). The spectral data matched those found in literature [3][4][5][6][7][8][9]27,35,36].…”
Section: Asymmetric Oxidation -Standard Proceduressupporting
confidence: 87%
See 2 more Smart Citations
“…Starting material 2 was recovered in 36% yield (72 mg). The spectral data matched those found in literature [3][4][5][6][7][8][9]27,35,36].…”
Section: Asymmetric Oxidation -Standard Proceduressupporting
confidence: 87%
“…The asymmetric oxidation of sulfide 2 was performed with Ti(iPrO) 4 /(+)-DET/TBHP in a ratio of 1:4:2 by using the known procedure [8]. The obtained results are presented in Table 1.…”
Section: Synthesis Of Enantioenriched 2-(s)-[(4-methylphenyl) Sulfiny...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, KshA3 is largely responsible for the initial specific 9α‐hydroxylation for the formation of 4 . To explore its specificity, substrate 5 was docked into the structural model of KshA3 generated by AlphaFold2 [19,20] . The analysis revealed that 5 was located within a hydrogen bond network consisting of residues I166, Y226 and N251, as well as a water molecule (Figure 3A).…”
Section: Resultsmentioning
confidence: 99%
“…9,11‐secosterols with unique broken tetracyclic carbon skeletons showcase a wide range of biological properties, encompassing antihistaminic, antiproliferative, anti‐inflammatory and protein kinase C(PKC) inhibition activities [13a–c] . A recent study conducted by Marek Kõllo and colleagues [13d] established a new route for chemoenzymatic synthesis of 9,11‐secosterols. This innovative approach involves using hydrocortisone ( 6 ), a commercially available compound, as the starting material, 9α‐hydroxylase (KshA5) can efficiently and selectively hydroxylate 11β‐hydrocortisone at C9.…”
Section: P450 Hydroxylase‐mediated Chemoenzymatic Synthesis Of Steroidsmentioning
confidence: 99%